TAMI-28. IDENTIFICATION OF A NEUROLIGIN-3 BINDING PARTNER IN HIGH-GRADE GLIOMAS AND NORMAL PROGENITORS. (12th November 2021) - Gillespie, Shawn; Kim, Yoon Seok; Geraghty, Anna; Quezada, Michael; Reed, James; Woo, Pamelyn; Monje, Michelle
Abstract: High-grade gliomas, including diffuse intrinsic pontine glioma, are lethal cancers whose progression is strongly regulated by neuronal activity. One way in which gliomas detect neuronal activity is via interaction with the ectodomain of post-synaptic adhesion protein neuroligin-3 (NLGN3), which is shed from neurons and oligodendrocyte precursors (OPCs) by the ADAM10 sheddase in an activity dependent manner. NLGN3 signaling drives glioma growth, but the cognate binding partner of shed NLGN3 (sNLGN3) on glioma cells is unknown. Here, we employed a proximity labeling technique to identify chondroitin sulfate proteoglycan 4 (CSPG4) as a putative binding partner of sNLGN3 in gliomas. We then confirmed complexing between recombinant proteins with size exclusion chromatography and are determining kinetics and affinity by surface plasmon resonance. When looking for evidence of binding in cells, we were surprised to find that sNLGN3 triggers regulated intramembrane proteolysis (RIP) of CSPG4, leaving no trace of the interaction at the membrane. sNLGN3 binding first induces ADAM10-mediated cleavage and release of the CSPG4 ectodomain, followed by gamma secretase-mediated release of the intracellular domain and downstream signaling in OPCs and gliomas. Pre-treatment of glioma cells or OPCs with an ADAM10 inhibitor entirely blocks sNLGN3-induced CSPG4 shedding. Acute depletion of CSPG4 via CRISPR gene editing renders glioma cells insensitive to the growth-promoting effects of sNLGN3 in vitro. Furthermore, we find that tamoxifen-induced deletion of NLGN3 from murine OPCs reduces the total number of OPCs, suggesting that this signaling axis promotes maintenance of OPC stemness in an autocrine fashion. Indeed, gamma secretase inhibition accelerates OPC differentiation in vitro, pointing towards a fundamental role for sNLGN3-CSPG4 signaling in OPCs and high-grade gliomas. Altogether, our results form a critical missing link in understanding how glioma cells detect a key neuronal activity-regulated signal, suggest intriguing links to OPC biology and identify a therapeutic target to disrupt neuron-glioma interactions.